2001
DOI: 10.5144/0256-4947.2001.304
|View full text |Cite
|
Sign up to set email alerts
|

Colonoscopy: Evaluating Indications and Diagnostic Yield

Abstract: Background: Colonoscopic procedure is an accepted modality for the evaluation of colonic disease. Open-access versus restricted-access colonoscopy has been argued over in the recent literature. The aim of this retrospective analysis is to identify the yield of the major indications for the procedure, and the pattern of colon pathology in our community. Patients and Methods:We retrospectively analyzed our experience in 3000 colonoscopies over a five-year period. The patients comprised 1145 females (38%) and 185… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 12 publications
(10 reference statements)
0
11
2
Order By: Relevance
“…This was similar to the observation in other studies conducted in other parts of the country,[1113] as well as those conducted in other parts of the world. [1214] However, in the study by Sayeed et al .,[10] in Bangladesh, the most common indication was clinical suspicion of IBS whereas, Sahu et al .,[9] in India, Ogutu et al .,[15] in Kenya and Al-Shamali et al .,[16] in Kuwait found lower abdominal pain to be the most common indication for colonoscopy.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This was similar to the observation in other studies conducted in other parts of the country,[1113] as well as those conducted in other parts of the world. [1214] However, in the study by Sayeed et al .,[10] in Bangladesh, the most common indication was clinical suspicion of IBS whereas, Sahu et al .,[9] in India, Ogutu et al .,[15] in Kenya and Al-Shamali et al .,[16] in Kuwait found lower abdominal pain to be the most common indication for colonoscopy.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, some studies in other parts of the world have reported much lower diagnostic yields than in this study. [912141619] Differences in indications, as well as the spectrum of colonic diseases in different parts of the world might also be of importance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…An earlier study from Kuwait[13] reported a prevalence of 4.6% for various types of colorectal polyps. In our study, the overall prevalence was comparatively higher.…”
Section: Discussionmentioning
confidence: 99%